Improved Bounds for Quaternary Linear Codes of Dimension 6. - Gulliver, T. Aaron (Applicable algebra in engineering, communication and computing.)
In this paper, twenty new codes of dimension 6 are presented which give improved bounds on the maximum possible minimum distance of quaternary linear codes. These codes belong to the class of quasi-twisted (QT) codes, and have been constructed using a stochastic optimization algorithm, tabu search. A table of upper and lower bounds for d 4(n,6) is presented for n≤ 200.